The feasibility study of stress position device simulating standing weight-bearing applied in computed tomography examination - Qiang Zhao; Yuhao Zhang; Xiaohui Gu (Journal of Orthopaedic Surgery, 2023)
Background In order to simulate weight-bearing Computed Tomography (CT) examination, this study designed a simple stress position device. By analyzing the relevant data of stress position footprints and weight-bearing position footprints, the feasibility of the stress position device to simulate standing weight-bearing was verified. Methods This study randomly selected 25 volunteers for standing weight-bearing and stress position footprints collection, and measured the relevant indicators of stress position footprints and standing weight-bearing position footprints. Two foot and ankle surgeons conducted two measurements respectively on the footprints. Intra-observer and inter-observer reliability were calculated using intra-class correlation coefficients (ICC). Pearson correlation coefficient, ICC, scatter plot analysis, and paired t -test were used to analyze the stress and weight-bearing position data. Results The intra-observer and inter-observer measurement values were reliable. There was a certain degree of correlation between the stress position footprints and weight-bearing position footprints in terms of Pearson correlation coefficient, ICC, and scatter plot analysis. Paired t-tests showed significant differences in Clarke angle (t 2.636, p .012), C-S index (t 10.568, p .000), arch indx (t 2.176, p .035), and arch lower angle (t 6.246, p .000). Conclusion The stress position device can generate a certain degree of stress, and after further optimization and improvement of the stress position device, it is feasible to apply it to weight-bearing CT examination in clinical settings.